Polish digit triplet test for auditory screening: development and initial evaluation - Edward Ozimek; Dariusz Kutzner; Aleksander Sęk; Andrzej Wicher (Archives of Acoustics, 2014)
The objective of this study was to develop and evaluate the Polish digit triplet test for speech intelligibility screening. The first stage of the work deals with the preparation of the test and the recording procedure. The second part presents results of the digit triplets intelligibility measurement and retest data. The test consists of 4 statistically equivalent and phonemically balanced lists, each containing 25 different triplets. The constant stimuli paradigm was used to determine the digit triplet psychometric functions. Fifty otologically normal subjects took part in the measurements. The mean list-specific SRT and $S_{50}$ for Polish digit triplet test are −9.4 dB and 19.7%/dB, respectively, and correlate very well with analogous parameters obtained for German digit triplet test, i.e. −9.3 dB and 19.6%/dB. The Polish digit triplet test evaluated in retest experiments revealed high reliability and accuracy for a fast intelligibility screening.